Historical contribution of road infrastructure investment on economic growth, production per worker and income per capita in Costa Rica - Cruz-Camacho, Camilo Santa (2025)
This paper tests the hypothesis of investment in road infrastructure affecting the economic growth of Costa Rica, from 1950 to 2017. To prove this, an economic growth function was estimated which, in addition to labor, private capital and human capital as inputs, it incorporates road capital under the approach of an atmosphere good that affects the economic dynamics. Results show a significant historical relationship between road infrastructure and economic growth, with elasticity estimates ranging from 0.12 to 0.21. These findings highlight the importance of increasing both the level and quality of investments to boost economic growth. Finally, the study suggests improvements in measurement methods and identifies future research directions.